Preparação, caracterização físico-química e avaliação do comportamento térmico e mecânico de blendas de poli (tereftalato de etileno) (PET) e poli (éterimidia) (PEI), PET/PEI - Barros, Adriana de Fátima (2004)
The blends preparation and composites have been one of the techniques more used to make possible properties and to increase the time of useful life of polymers. PET is a polymeric semicrystalline that has a Tg in 75°C and Tm in 245°C. The low value of Tg of PET and its easiness in crystallizing a lot of times points negative not desired can be considered in a certain project. PEI is a polymeric one amorphous with a value of Tg quite loud 215°C. In the mixture of PET (virgin or recycled) with PEI a displacement was verified in Tg of PET, as well as the one of PEI suggesting polymeric miscibility of the two in the melted state and confirmed later on by the negative value of the parameter of certain Flory to thermal treatments. Since the fusion entalpia is proportional to the crystalline fraction, its correlation with the conformer Reason Trans, RT, was found linear and independent of the content of PEI, turning possible to the determination of the degree of cristalinidade of independent PET of which it goes the composition of to blend PET/PEI. From the results of mechanical resistance of the samples submitted to the aging under radiation UV, it was verified that, independent of the type of PET employee, of the time of radiation of the condition dry or after immersion in water, for stabilized blends or not, so much the specific deformation in the rupture, elastic module, the deformation, and calculated elastic energy, they show a continuous tendency of growth with increase of the content of PEI in the mixture. The effective protection of PEI was verified on PET starting from 25% in PEI of up to 200h of exhibition under UV for the dry samples and up to 100h for samples after immersion in water. After thermal cycle it was verified that, depending on the temperature of the test the composition becomes an important factor. The thermal treatment above 90°C in the presence of the blends with larger concentration than 25% in PEI eliminate the tensions frozen during the processing, in other words, physical aging without there is the crystallization of PET, consequently, a significant improvement was observed in the mechanical answer in terms of elastic energy until tenth cycle. The thermal cycle at 120°C and 140°C is committed for the physical aging of PET and crystallization after the first cycle. The results obtained for the blend with content of 25% in PEI, in fact, when compared to the samples of pure PET they evidence the significant gain in the value of the elastic energy, these results suggest the potentiality for a possible application of this blend in the production of pieces whose interest is to guarantee a good resistance to the impact.